Role for the adenovirus IVa2 protein in packaging of viral DNA - Zhang, W; Low, J A; Christensen, J B; Imperiale, M J (Journal of virology, 2001)
Although it has been demonstrated that the adenovirus IVa2 protein binds to the packaging domains on the viral chromosome and interacts with the viral L1 52/55-kDa protein, which is required for viral DNA packaging, there has been no direct evidence demonstrating that the IVa2 protein is involved in DNA packaging. To understand in greater detail the DNA packaging mechanisms of adenovirus, we have asked whether DNA packaging is serotype or subgroup specific. We found that Ad7 (subgroup B), Ad12 (subgroup A), and Ad17 (subgroup D) cannot complement the defect of an Ad5 (subgroup C) mutant, pm8001, which does not package its DNA due to a mutation in the L1 52/55-kDa gene. This indicates that the DNA packaging systems of different serotypes cannot interact productively with Ad5 DNA. Based on this, a chimeric virus containing the Ad7 genome except for the inverted terminal repeats and packaging sequence from Ad5 was constructed. This chimeric virus replicates its DNA and synthesizes Ad7 proteins, but it cannot package its DNA in 293 cells or 293 cells expressing the Ad5 L1 52/55-kDa protein. However, this chimeric virus packages its DNA in 293 cells expressing the Ad5 IVa2 protein. These results indicate that the IVa2 protein plays a role in viral DNA packaging and that its function is serotype specific. Since this chimeric virus cannot package its own DNA, but produces all the components for packaging Ad7 DNA, it may be a more suitable helper virus for the growth of Ad7 gutted vectors for gene transfer.